(untitled) - Simmonds, John (Oxford,Ames, Iowa, 2005)
"The new volume of Fisheries Acoustics captures the advances in the technology associated with the use of acoustics to find, classify, size, enumerate, examine the behaviour of, and help manage various types of fish."
Keywords: Fishes; Detection.,Đánh bắt cá